Advances in computational intelligence systems : contributions presented at the 16th UK Workshop on Computational Intelligence, September 7-9, 2016, Lancaster, UK /: contributions presented at the 16th UK Workshop on Computational Intelligence, September 7-9, 2016, Lancaster, UK. ([2017]) - Unknown
No abstract available